The Effect of Accounting Understanding, Utilisation of Accounting Information Systems and Internal Control Systems On The Quality of Government Financial Reports - Kuntadi, Cris; Livrianti, Nurma (Green Publisher, 2023)
In a scientific piece, prior research is crucial. The theory and phenomenon behind therelationship or influence between variables are strengthened through pertinent study. This article analyses research on the impact of accounting knowledge, the use of accounting information systems, and internal control systems on the accuracy of government financial reporting. In order to create hypotheses of effect between factors that might be employed in future study, this article does a literature review. The quality of government financial reports is affected by accounting knowledge, the use of accounting information systems, and internal control systems, as this article demonstrates.